Evaluación de la resistencia a la compresión de la resina compuesta nanohíbrida con microrelleno de zirconio/sílice fotopolimerizadas con dos lámparas led de alta intensidad - Rodríguez Salcedo, Diego Orlando (2020)
Introduction: The ability to photopolymerize composite resins directly in the mouth has revolutionized clinical dentistry when working on the patient. However, there is a lack of understanding when choosing a photopolymerization lamp that achieve a successful outcome for the clinician. Objective: To evaluate the compressive resistance of the photopolymerized zirconium / silica micro-filled Nanohybrid Composite Resin with two high power LED lamps. Materials and Methods: With a calibrated metal matrix, 20 resin-based composites (RBCs) of 8mm high and 4mm in diameter were elaborated, the resin was placed in 2mm increments and then polymerized according to the study group. There were 10 polymerized RBCs with a 1280mW / cm2 lamp (VALO, ULTRADENT) and 10 RBCs with a 1260mW / cm2 lamp (S.P.E.C. 3, COLTENE) measured with a radiometer on a resin of the Filtek 350 brand (3MESPE ). The samples were immersed in distilled water at 37 Celsius degrees for 24 hours; then it was subjected to a careful polishing of the surfaces. After a process of calibration and evaluation of the dimensions of each RBCs, these were sent to a universal compression machine MTS JJ MACHINE TYPE T5002 of the Research Center of the Honorable Provincial Government of Tungurahua (Metalworking Productive Development Center). One-way ANOVA was used to evaluate the results. Results: The compression values proved to be different between the groups studied. The S.P.E.C. 3 is significantly superior to the VALO lamp (p equals 0.016). Conclusions: The compressive strength of the Composite Nanohybrid Resin with zirconium / silica micro-fill obtained a better performance when subjected to photopolymerize with the Spect3 Lamp.